2014
DOI: 10.23939/chcht08.04.445
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of Polymeric Composition Filled with Ground Tire Rubber – Short Review

Abstract: Waste rubber is recognized as a valuable materials resource and searching for new recycling methods is the main activity of many research institutions and companies. During last years only few scientific papers concerning foamed polymer compositions filled with ground tire rubber were published. The paper reviews the progress in compatibilization and foaming of polymeric compositions filled with a ground tire rubber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The interaction of the maleic anhydride group (MAPE) with the hydroxyl group on the carbon black surface or carboxyl groups of RR may be responsible for interfacial interaction between rubber and compatibilizer. 44,45 It is also reported that possible reaction between zinc oxide (ZnO) as a component of RR (Table 3) with maleic anhydride (MA) during melt mixing can be responsible for the tensile strength improvement of compatibilized TPE blends. 46…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of the maleic anhydride group (MAPE) with the hydroxyl group on the carbon black surface or carboxyl groups of RR may be responsible for interfacial interaction between rubber and compatibilizer. 44,45 It is also reported that possible reaction between zinc oxide (ZnO) as a component of RR (Table 3) with maleic anhydride (MA) during melt mixing can be responsible for the tensile strength improvement of compatibilized TPE blends. 46…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of the maleic anhydride group (MAPE) with the hydroxyl group on the carbon black surface or carboxyl groups of RR may be responsible for interfacial interaction between rubber and compatibilizer. 44,45 It is also reported that possible reaction between zinc oxide (ZnO) as a component of RR (Table 3) with maleic anhydride (MA) during melt mixing can be responsible for the tensile strength improvement of compatibilized TPE blends. 46 The increase in RR content from 35 wt.% to 80 wt.% showed a significant decreasing trend of Young's modulus from 191.2 MPa to 32.5 MPa attributed to the substitution of the rigid thermoplastic resin with a soft rubber phase of low rigidity.…”
Section: Mechanical (Tension and Flexion) Propertiesmentioning
confidence: 99%